Publishing and the Academic World: Passion, purpose and possible futures - Sugrue, Ciaran; Mertkan, Sefika (Taylor and Francis, 2016)
Within the Academy, itself a changing and increasingly entrepreneurial entity, publishing is no longer an option; it is the universal currency that secures a position, tenure and promotion; it is key to academic life. Providing a panoramic picture of the changing publishing climate, Academic Life and the Publishing Landscape will empower scholars by enabling them to navigate this changing terrain more successfully. This book provides guidance from a range of contributors who use their own wide expertise in writing and publication to document the challenges faced by scholars at different career stages and in different locations. It covers a wide range of debates on publishing, spilt into the following three sections: •Mapping the Publication Landscape, •Writing for Publication-Learning from Successful Voices, •Further Challenges and Possibilities. With topics ranging from the process of preparing manuscripts for publication, including chapters on calculating journal rankings and understanding the Peer Review process, through to chapters on speaking to international audiences and writing for elite international journals, this book offers a unique perspective on how the changing nature of publishing works. This will be a useful guide for scholars across the globe looking to enhance their publication performance, and those questioning what needs to be done in order to understand, navigate and to (re-)position one’s self and institution in this increasingly significant and rapidly altering terrain. Ciaran Sugrue is Professor of Education, University College Dublin, Ireland and has been Head of School from 2011-14. Sefika Mertkan is an Assistant Professor of Educational Leadership and Management at Eastern Mediterranean University. © 2016 selection and editorial matter, Ciaran Sugrue and Sefika Mertkan.